1990
DOI: 10.1007/bf00400568
|View full text |Cite
|
Sign up to set email alerts
|

A new non-invasive method for treating insulin-reaction: intranasal lyophylized glucagon

Abstract: The main therapeutic indication for glucagon is the treatment of hypoglycaemia in insulin overdosed Type 1 (insulin-dependent) diabetic patients. We have previously shown that an intranasal spray of 7.5 mg glucagon with deoxycholic acid as surfactant was able to correct an i.v. insulin-induced hypoglycaemia in diabetic patients. However, bioavailability and stability needed to be improved before intranasal glucagon could be introduced into clinical practice. This has now been achieved with a freeze-dried mixtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 8 publications
3
15
0
Order By: Relevance
“…As previously reported in studies of children [11,14] and adults [13], glucagon treatment is accompanied by the late development of marked nausea. In this study we found that almost all the children developed nausea 90-120 rain after the s.c. injection of glucagon.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…As previously reported in studies of children [11,14] and adults [13], glucagon treatment is accompanied by the late development of marked nausea. In this study we found that almost all the children developed nausea 90-120 rain after the s.c. injection of glucagon.…”
Section: Discussionsupporting
confidence: 54%
“…Like others [13,22], we found that the peak of i. n. glucagon concentration occurred earlier following i.n. administration and that it fell more rapidly than that following s. c. glucagon administration.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Measure of efficacy was the number/percentage of patients/subjects not responding to glucagon according to criteria pre-defined by the authors of each paper. All the data are tabulated in Tables 1 and 2. Sixteen studies fulfilled the inclusion criteria [33,42,44,[50][51][52][53][54][55][56][57][58][59][60][61][62]. Details of data source and searches, study selection, data extraction and quality assessment, data synthesis, ER emergency room, SH severe hypoglycemia, IV intravenous, IM intramuscular; AEs adverse events, FDA food and drugs administration, EMS emergency medical services, and NEMSIS national emergency medical services information system and analysis have already been published [12].…”
Section: Methodsmentioning
confidence: 99%
“…22 Studies performed later showed that glucagon solutions and powders were similarly effective, provided a promoter was present (sodium glycocholate, 9-lauryl ether, deoxycholic acid, didecanoyl phosphatidylcholine [DDPC] with alpha-cyclodextrine, sodium caprate, microcrystalline cellulose). [23][24][25][26] Eventually, several authors showed the ability of IN glucagon to resolve hypoglycemia in normal volunteers and in diabetic patients, adults, and children. [25][26][27][28][29][30][31][32] These studies, which encompass almost 300 study subjects, demonstrate that glucagon is well-suited for IN administration.…”
Section: Intranasal Glucagonmentioning
confidence: 99%